The Use of E-learning Modules to Improve Student Knowledge in Obstetrics and Gynecology - Carmen Obando; Joel Maurer; Geraud Plantegenest; Christina Dokter (Association of American Medical Colleges, 2014)
Abstract Introduction The Obstetrics and Gynecology e-learning modules included in this resource are a set of three interactive self-directed learning instruments that offer alternative explanations of three different clinical case scenarios: amenorrhea, vaginitis, and third-trimester bleeding. These three topics were found to be rare in some clinical settings, thus making it difficult for students to observe them during their rotations. Methods These modules allow students to observe patient-physician interactions and to identify symptoms and alternative diagnoses by using photos, videos, graphics, animations, text, and notes. The time needed to review each module varies by student. A student can take as much time as needed for each of the components and view them in the order desired. Results Students' feedback suggests that they liked the availability of the modules as an online resource they could access at any time to review as many times as they needed. The interaction and self-directed characteristics of the modules also allowed the students to learn at their own pace. Discussion The use of these modules reduces learning disparities by creating standardized simulated cases regardless of the number of cases encountered during the clerkship. The modules are accessible 24/7 to all students going through the OB-GYN clerkship and to faculty and staff through our departmental website, and students are required to review them before their hands-on experience. One of the limitations imposed by the use of online teaching materials is the lack of live interaction with an instructor. This can be easily compensated for by complementing use of the modules with a face-to-face interaction with the preceptor to review concepts not well understood by the student and to obtain feedback on any of the clinical cases presented.